GENDER DISCRIMINATION IN MATHEMATICS TEACHING: A SYSTEMATIC REVIEW - Bustos Mancera, Luis Alejandro (2025)
The purpose of this article is to analyze the categories present in the research on gender discrimination in mathematics teaching with a narrative approach based on a systematic review. It presents a contextualization of the research problem, some theoretical elements, and methodological aspects of the way in which the selected articles and theses were selected and organized using the PRISMA protocol. Then, the categories that encompass most of these investigations are presented: experience, representation, trajectory and positioning. In addition, an analysis of the gender perspectives and narrative approaches present in these sources is presented. It concludes with some recommendations for future research on the topic.